Usulan Pengurangan Downtime Mesin Oil Expeller PT. Sari Mas Permai - Gunawan, Kevin Pranata; Yang Aysia, Debora Anne (Jurnal Titra, 2015)
PT. Sari Mas Permai is a company that produces cooking oil from coconut fruit and also palm coconut. Plant 1 located in PT. Sari Mas Permai has lots of manual machinery and applying breakdown maintenance. This system makes more workload due to unplanned breakdown. Suggestion for company is designing new job desc, early spare part production, and applying preventive maintenance using MTTF for each component. New job desc could decrease repair time to 137 minutes. Preventive maintenance plans for long axel and drig laker, need to be replaced every 15 and 62 days.